Determinação por RMN das configurações relativas e conformações de alcalóides oxindólicos isolados de Uncaria guianensis - Carbonezi, Carlos Alberto [UNESP] (2004)
Phytochemical studies with leaves of Uncaria guianensis resulted in the isolation of the oxindole alkaloids isomitraphylline (1), 3-isoajmalicine (2) mitraphylline (3), and isomitraphylinic acid (4). Structural assignments of these alkaloids, including relative configurations and conformations, were performed through spectral data and physical properties. 1D and 2D homonuclear and heteronuclear NMR spectroscopy was a valuable tool for the establishment of the relative stereochemistry of those compounds.